Machining Aspects of Al2O3 Nano Cutting Fluids – A Comparative Study - Mukkamala Usha; Gunji Srinivasa Rao (Tribology in Industry, 2022)
Health and environmental concerns on usage and disposal of cutting fluids during machining has led to development of minimum quantity lubrication (MQL) technique which requires specialized fluids having superior properties. Nano particle-based lubricating fluids have been found to satisfy the properties for cutting fluids used in MQL. Nano particles are synthesized using various techniques. Herbal based synthesis is a recent advancement in preparation of nano particles. In the present work, fluids prepared from herbal based synthesis was compared with non-herbal synthesis, and were evaluated for their lubricating properties like thermal conductivity and viscosity. Both fluids were used in turning process via MQL and measurements were taken of the cutting forces and surface roughness. Regression equations were developed and 3D surface graphs were drawn for the measured responses among herbal nanofluid, non-herbal nanofluid and dry machining. Based on the analysis, herbal based nanofluid showed improvement in the responses compared to non-herbal synthesized nano fluid and also when compared to dry machining.